Comprehensive Health‐State Utilities in Contemporary Patients With Cirrhosis - Foster, Chelsey (Hepatol Commun, 2020)
Cost‐effectiveness analysis depends on generalizable health‐state utilities. Unfortunately, the available utilities for cirrhosis are dated, may not reflect contemporary patients, and do not capture the impact of cirrhosis symptoms. We aimed to determine health‐state utilities for cirrhosis, using both the standard gamble (SG) and visual analog scale (VAS). We prospectively enrolled 305 patients. Disease severity (Child‐Pugh [Child] class, Model for End‐Stage Liver Disease with sodium [MELD‐Na] scores), symptom burden (sleep quality, cramps, falls, pruritus), and disability (activities of daily living) were assessed. Multivariable models were constructed to determine independent clinical associations with utility values. The mean age was 57 ± 13 years, 54% were men, 30% had nonalcoholic steatohepatitis, 26% had alcohol‐related cirrhosis, 49% were Child class A, and the median MELD‐Na score was 12 (interquartile range [IQR], 8‐18). VAS displayed a normal distribution with a wider range than SG. The Child‐specific SG‐derived utilities had a median value of 0.85 (IQR, 0.68‐0.98) for Child A, 0.78 (IQR, 0.58‐0.93) for Child B, and 0.78 (IQR, 0.58‐0.93) for Child C. VAS‐derived utilities had a median value of 0.70 (IQR, 0.60‐0.85) for Child A, 0.61 (IQR, 0.50‐0.75) for Child B, and 0.55 (IQR, 0.40‐0.70) for Child C. VAS and SG were weakly correlated (Spearman's rank correlation coefficient, 0.12; 95% confidence interval, 0.006‐0.23). In multivariable models, disability, muscle cramps, and MELD‐Na were significantly associated with SG utilities. More clinical covariates were significantly associated with the VAS utilities, including poor sleep, MELD‐Na, disability, falls, cramps, and ascites. Conclusion: We provide health‐state utilities for contemporary patients with cirrhosis as well as estimates of the independent impact of specific symptoms on each patient’s reported utility.